Polysaccharide stabilized nanoparticles for deacidification and strengthening of paper1. Issue 42 (10th May 2015) - Amornkitbamrung, Lunjakorn; Mohan, Tamilselvan; Hribernik, Silvo; Reichel, Victoria; Faivre, Damien; Gregorova, Adriana; Engel, Patricia; Kargl, Rupert; Ribitsch, Volker
<x xml:space="preserve">Abstract</x> This paper reports an investigation on the use of a highly stable colloidal organic dispersion consisting of a polysaccharides and alkaline nanoparticles for the simultaneous deacidification and strengthening of historical wood pulp papers.